2012
DOI: 10.1155/2012/616383
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry and the Improvement of Soil Fertility: A View from Amazonia

Abstract: This paper discusses the effects of trees on soil fertility, with a focus on agricultural systems in Amazonia. Relevant literature concerning the effects of trees on soil physical and chemical properties in tropical, subtropical, and temperate regions is reviewed, covering both natural ecosystems and agroecosystems. Soil carbon, in the form of organic matter, is considered as an indicator of biological activity as well as in relation to policy issues such as carbon sequestration and climate change. In the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 57 publications
6
63
0
7
Order By: Relevance
“…Leguminous trees within dryland agroforestry systems contribute to soil fertility by fixing atmospheric nitrogen and inputting into the soil, retrieving of nutrients from below the rooting zone of crops, and reducing nutrient losses from leaching and erosion (Buresh and Tian 1998). The woody component can also provide possibilities for the use of green and animal manure for the amelioration of the soil (Pinho et al 2012;Marques et al 2016). In addition, agroforests enhance the diversity and abundance of the soil biota and nutrient cycling.…”
Section: Rehabilitation Of Degraded Croplandsmentioning
confidence: 99%
“…Leguminous trees within dryland agroforestry systems contribute to soil fertility by fixing atmospheric nitrogen and inputting into the soil, retrieving of nutrients from below the rooting zone of crops, and reducing nutrient losses from leaching and erosion (Buresh and Tian 1998). The woody component can also provide possibilities for the use of green and animal manure for the amelioration of the soil (Pinho et al 2012;Marques et al 2016). In addition, agroforests enhance the diversity and abundance of the soil biota and nutrient cycling.…”
Section: Rehabilitation Of Degraded Croplandsmentioning
confidence: 99%
“…This influence is mainly due to large amounts of household organic waste that is deposited in these areas due to proximity to homes [35]. [36] noted that indigenous agroforestry systems around dwellings in the savanna region of Roraima state resulted in an improvement in soil chemical properties over time, mainly due to management practices related to organic waste deposition and the burning of plant residues. Similar results were obtained by [37] in indigenous homegardens in the Central Amazon region.…”
Section: Soil Fertilitymentioning
confidence: 99%
“…Hence, roots may supply more stable C to the soil as observed by Makumba et al (2007) studying the effect of agroforestry practice on C sequestration and CO2-C efflux in a gliricidia-maize intercropping system. Lenka et al (2012) and Pinho et al (2012) have suggested that AFSs, especially with the insertion of trees, have higher potential to build up and sequester C in soils because of the increased rates of organic matter addition and retention. However, according to Derpsch (2008), clear increases in soil organic matter only appear 5-10 years after the adoption, as verified in the AFS13 system.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it can be efficient marker of soil history (it suffers influences of soil formation factors like time, origin material, climate, relief and anthropomorphic action) assuming a key role (especially humic acids) as indicators of SOM quality, since during the humification process (organic residues stabilization), the humified fraction is the one that undergoes the largest structural change (CANELLAS et al, 2004;MARTINS et al, 2009;PESSOA et al, 2012). Therefore, changes in ûeld management practices, such as AFS, can alter the chemical properties of soil humic substances (MORAES et al, 2011;GUIMARAES et al, 2013) Several studies have been published in Brazil linking soil properties and AFS although most of them are concentrated in the Amazon region and featured to the soil chemical and physical attributes (SCHROTH et al, 2002;BARROS et al, 2004;BARRETO et al, 2006;PEREIRA et al, 2008;PINHO et al, 2012) with few focusing SOM pools dynamic MORAES et al, 2011;ZAIA et al, 2012). Therefore, our objective was to evaluate the influence of AFS, established in long-term, on SOM pools in a tropical soil from Northeast Brazil.…”
Section: Introductionmentioning
confidence: 99%